Neisseria gonorrhoeae NGO2105 Is an Autotransporter Protein Involved in Adhesion to Human Cervical Epithelial Cells and in vivo Colonization - Huang, Jian; Zhang, Qing; Chen, Jie; Zhang, Tao; Chen, Zehui; Chen, Zuyi; Yang, Jianru; Wang, Yongxiang; Min, Zongsu; Huang, Meirong; Min, Xun (Frontiers in Microbiology, 2020)
Autotransporters are important virulence factors in the outer membrane of gram-negative bacteria. Although several autotransporters have been identified in Neisseria meningitidis, only IgA1 protease has been identified in Neisseria gonorrhoeae. A sequence analysis showed a marked difference in the distribution of autotransporters between the two strains. It has been speculated that only two autotransporters, the IgA1 protease and the NGO2105 protein, might be encoded by N. gonorrhoeae. Here, we describe the identification of NGO2105, a new autotransporter in N. gonorrhoeae. A sequence alignment showed that NGO2105 is highly similar to the adhesion and penetration protein (App) in N. meningitidis. We found that NGO2105 is exported to the outer membrane, cleaved and released into the culture supernatant by endogenous serine protease activity in N. gonorrhoeae and E. coli. The site-directed mutagenesis of S267A in the predicted enzyme catalytic triad abolished autoproteolytic cleavage to allow secretion. The NGO2105 β-barrel shows the ability to translocate the heterologous Hbp passenger domain. NGO2105 is involved in gonococcal adherence to and invasion into human cervical epithelial cells. Furthermore, antibodies raised against NGO2105 are able to block gonococcal adherence to human cervical epithelial cells. The Δngo2105 mutant and anti-NGO2105 antiserum significantly attenuated the colonization of N. gonorrhoeae in mice. Collectively, our results suggest that the newly identified serine protease autotransporter NGO2105 represents a novel virulence factor of gonococcus and a potential vaccine target.